Education and digital technologies from the epistemológical base of paulo freire: Systematic literature review in SciELO database - Fernando Gomes, Marcio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The aim is to relate education based on Paulo Freire’s epistemological basis with digital technologies. The question is: in what conditions does Paulo Freire’s epistemological basis become a fundamental reference of educational processes that have incorporated digital technologies? First, a simple literature review is carried out. Second, a systematic literature review is carried out in SciELO database, between 1995 and 2021, in 21 articles to compose the meta-study: metatheory; metamethods; meta-analysis; and metasynthesis. It is concluded that despite being a little researched theme, there are many possibilities to relate Freirian dialogical pedagogical innovations associated with the critical use of technological innovations.